2022
DOI: 10.3390/nano12071187
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mn3O4-CeO2-rGO as Nanocatalyst for Electro-Oxidation of Methanol

Abstract: Recently, the use of metal oxides as inexpensive and efficient catalysts has been considered by researchers. In this work, we introduce a new nanocatalyst including a mixed metal oxide, consisting of manganese oxide, cerium oxide, and reduced graphene oxide (Mn3O4-CeO2-rGO) by the hydrothermal method. The synthesized nanocatalyst was evaluated for the methanol oxidation reaction. The synergetic effect of metal oxides on the surface of rGO was investigated. Mn3O4-CeO2-rGO showed an oxidation current density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The outstanding properties of this 2D material have led to many application proposals. To cite just a few of them: nanocomposites for bone tissue engineering [3], composites for multifunctional applications [4], lubrication [5,6], solar cells [7], ultracapacitors [8,9], batteries [10], sensors [11], catalysis [12], nanomedicine [13], fuel cells [14,15] or even energy harvesting [16].…”
Section: Introductionmentioning
confidence: 99%
“…The outstanding properties of this 2D material have led to many application proposals. To cite just a few of them: nanocomposites for bone tissue engineering [3], composites for multifunctional applications [4], lubrication [5,6], solar cells [7], ultracapacitors [8,9], batteries [10], sensors [11], catalysis [12], nanomedicine [13], fuel cells [14,15] or even energy harvesting [16].…”
Section: Introductionmentioning
confidence: 99%
“…Askari et al [20] reported the one-step preparation by the hydrothermal method of Mn 3 O 4 -CeO 2 mixed metal oxides and reduced graphene oxide (rGO) hybrid catalysts to be used in the methanol oxidation reaction (MOR) process. Interestingly, the authors remarked the occurrence of a synergetic effect occurring between rGO and Mn 3 O 4 -CeO 2 .…”
Section: Commenmentioning
confidence: 99%
“…[ 31 ] Moreover, due to high surface area, rGO can be an attractive choice for promoting the electrocatalytic effects of metal oxide composites. [ 32,33 ]…”
Section: Introductionmentioning
confidence: 99%
“…[31] Moreover, due to high surface area, rGO can be an attractive choice for promoting the electrocatalytic effects of metal oxide composites. [32,33] In this study, NiO-Co 3 O 4 (NC) and NiO-Co 3 O 4 -rGO (NCR), as two metal component nanocatalysts, were synthesized by a hydrothermal method and the structure of the nanomaterials was characterized by complementary techniques. The synergistic effect of NiO and Co 3 O 4 together and the hybridization of these efficient metal oxides with rGO led to the fabrication of a cheap, stable and sensitive electrochemical sensor for nitrite detection in beef and tap water as real samples.…”
Section: Introductionmentioning
confidence: 99%